PROFIL KANDUNGAN KIMIA DAN POTENSI TUMBUHAN MANGGIS HUTAN (Garcinia Bancana Miq.) SEBAGAI SUMBER SENYAWA ANTIOKSIDAN - Muharni, Muharni (Publikasi Penelitian Terapan dan Kebijakan, 2010)
Garcinia bancana belonging to the Guttiferae family,in Indonesia this plant is locally named manggis hutan. In order to our profile of chemical compounds and biology activity of Garcinia plants which found in Indonesia six compounds from the stem bark and two compound from the leaves were isolated of Garcinia bancana. Isolated by chromatography technique and The structure of these compound were determined base on spectroscopic data including UV, IR, NMR 1-D and 2-D. Based on spectroscopy data the eight compounds are 1,5-dihydroxy-3,6- dimethoxy-2,7-di-(3-methylbut-2-enyl)xanthone (1), 1,4,6-trihydroxy,3-methoxy,5-(3methylbut-2- enyl)xanthone (2), isoxanthochymol (3), (-)-epicathechin (4), β-amyrin (5), 1,5-dihydroxy-6’,6’- dimehylpyrano (2’, 3’: 2,3) xanthone (6). lupeol (7) and apygenin (8). All compound were determined antioxidant activity by 1,1-diphenyl-2-picrylhydrazyl radical (DPPH). Three compounds of isoxanthochymol (3).(-)-epicathechin (4) and 1,5-dihydroxy-6’,6’-dimehylpyrano (2’, 3’: 2,3) xanthone (6) showed the active antioxidant with IC50 value of 9.8 ; 8.1; and 68 μg/mL respectively